A Janus-paper PDMS platform for air–liquid interface cell culture applications. (17th April 2015) - Rahimi, Rahim; Ochoa, Manuel; Donaldson, Amy; Parupudi, Tejasvi; Dokmeci, Mehmet R; Khademhosseini, Ali; Ghaemmaghami, Amir; Ziaie, Babak
Abstract: A commercially available Janus paper with one hydrophobic (polyethylene-coated) face and a hygroscopic/hydrophilic one is irreversibly bonded to a polydimethylsiloxane (PDMS) substrate incorporating microfluidic channels via corona discharge surface treatment. The bond strength between the polymer-coated side and PDMS is characterized as a function of corona treatment time and annealing temperature/time. A maximum strength of 392 kPa is obtained with a 2 min corona treatment followed by 60 min of annealing at 120 °C. The water contact angle of the corona-treated polymer side decreases with increased discharge duration from 98° to 22°. The hygroscopic/hydrophilic side is seeded with human lung fibroblast cells encapsulated in a methacrylated gelatin (GelMA) hydrogel to show the potential of this technology for nutrient and chemical delivery in an air–liquid interface cell culture.